Development of a Spatial Decision Support System (SDSS) for the active forest-urban fires management through location planning of mobile fire units. (14th March 2020) - Sakellariou, Stavros; Samara, Fani; Tampekis, Stergios; Sfougaris, Athanasios; Christopoulou, Olga
ABSTRACT: Critical time of response constitutes the foundation for effective and timely forest fires management. It is the milestone for strategic and operational fire planning. Aim of the paper is the development of a Spatial Decision Support System (SDSS) adopting a top-down approach for the immediate containment of forest and urban fires. The objectives lie in the coupling of strategic and operational nature of fire management, so that the proposed model to be used for real-time purposes. The strategic dimension focus on the location-allocation of fire vehicles to establish effective location schemes adjusted to population dynamics (Wildland Urban Interface). Four spatial patterns of optimal locations were developed based on ideal and realistic critical time of response as well as the current and desired capacity of fire agency. The operational dimension supports the strategic planning objectives through a series of additional sub-models for a second phase optimization (activating and leading the nearest fire vehicle(s) to the affected area through the determination of optimal route; and/or the rerouting in case of road closure due to evolving fires). Therefore, the current SDSS handles the forest and urban fires management in a more comprehensive way, creating an effective link between strategic and operational level.